Upgrading of Alum Preparation and Dosing Unit for Sharq Dijla Water Treatment Plant by Using Programmable Logic Controller System (Journal of Engineering, 2018)
One of the important units in Sharq Dijla Water Treatment Plant (WTP) first and second extensions are the alum solution preparation and dosing unit. The existing operation of this unit accomplished manually starting from unloading the powder alum in the preparation basin and ending by controlling the alum dosage addition through the dosing pumps to the flash mix chambers. Because of the modern trend of monitoring and control the automatic operation of WTPs due to the great benefits that could be gain from optimum equipment operation, reducing the operating costs and human errors. This study deals with how to transform the conventional operation to an automatic monitoring and controlling system depending on a Programmable Logic Controller (PLC) and online sensors for alum preparation and dosing unit in Sharq Dijla WTP. PLC system will receive, analyze transmitting data, compare them with preset points then automatically orders the operational equipment (such as pumps, valves, and mixers) in a way that guarantees the safe and appropriate operation of the unit. As a result of Process and Instrumentation Diagrams (PID) that were prepared in this study, these units can be fully operating and manage by using Supervisory Control and Data Acquisition (SCADA) system.